Analysis of Village Fund Management in Village Development and Community Empowerment (Analytical Study in Tanjung Pura District, Langkat) - Akbar, Akbar; Ridwan, M.; Bara, Maryam Batu (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
This study aims to analyze the Analysis of Village Fund Management in the development and empowerment of village communities that require adequate funds as support for the implementation of authority. The problem in Teluk Desa Baja Kuning and Pematang Serai Bakung Village, Tanjung Pura District, Langkat Regency is that Village Fund Management has not been able to carry out its functions optimally due to the uneven distribution of development and the lack of empowerment programs in the Teluk Desa Baja Kuning and Pematang Serai Bakung Village, Tanjung Pura District, Langkat Regency. The purpose of the study was to determine the strategy for managing village funds to improve development and community empowerment in Teluk Desa Baja Kuning and Pematang Serai Bakung Village, Tanjung Pura District, Langkat Regency. This research method is qualitative research. The results of the study showed that the village community development strategy by conducting Village Development Planning Deliberations consisted of the planning stage, implementation stage, and evaluation stage. Economic empowerment carried out in Teluk Desa Baja Kuning and Pematang Serai Bakung Village, Tanjung Pura District, Langkat Regency was empowerment in physical form, and empowerment in non-physical form. The impact of using village funds consists of positive and negative impacts.